KECERDASAN EMOSIONAL, MOTIVASI, DAN INSENTIF PEKERJA TETAP PT. BANK RAKYAT INDONESIA KANTOR CABANG PALU - Yanuar, Mohammad (Katalogis, 2018)
The aim of this study are: 1) to Find out simultaneous influence of emotional quotient, motivation, and incentive on staff’s performance in PT.BRI Branch Of Palu; 2) to Find out Partial influence of emotional quotient on staff’s performance in PT.BRI Branch Of Palu; 3) to Find out Partial influence of motivation on staff’s performance in PT.BRI Branch Of Palu; 4) to Find out Partial influence of Incentive on staff’s performance in PT.BRI Branch Of Palu. Type of study is casual descriptive that determine the raltion among variables by involving 169 respondents who were selected through census technique. Based on the test result with multiple inear regression analysis, this study condludes that: 1) emotional quotient, motivation, and incentive simultaneously have significant influence on staff’s performance in PT. BRI Branch Of Palu; 2) emotional quotient has significant influence on staff’s performance in PT. BRI Branch Of Palu; 3) Motivation has significant influence on staff’s performance in PT. BRI Branch Of Palu; 4) Incentive has significant influence on staff’s performance in PT. BRI Branch Of Palu;